THE EFFECT OF DIACEREIN AND MELOXICAM COMBINATION VERSUS MELOXICAM ALONE ON PHYSICAL FUNCTION IN PATIENTS WITH KNEE OSTEOARTHRITIS - Dwicandra, Ni Made Oka; Jaya, Made Krisna Adi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: More than 50% of patients with knee osteoarthritis (OA) had an inadequate pain relief in its management. Combination therapy could be the solution to this problem. The aim of this study was to compare the efficacy of combination therapy of diacerein and meloxicam with meloxicam alone in the patient with knee OA. Methods: A total of 64 knee OA patients were recruited from Rumah Sakit Umum Daerah Dr. Mohammad Soewandhie Surabaya. They were allocated to combination group and single therapy group using randomized controlled trial design. The Western Ontario and McMaster Universities Arthritis Index (WOMAC) physical function questionnaire were assessed in weeks 0–4th. The difference between pre- and post-treatment score and area under the curve (AUC) of WOMAC score were calculated. Results: Combination therapy and single therapy had significant clinical effect with the downregulated score of WOMAC physical function after 4th week (p<0.05). However, there were no differences in AUC of WOMAC physical function score between combination and single therapy. Conclusion: Patient with knee OA could gain beneficial efficacies from combination therapy of diacerein and meloxicam. Studies of longer follow-up time to get the differences in AUC of WOMAC physical function score are needed.